Adaptation and the distributional effects of heat: Evidence from professional archery competitions. (10th December 2021) - Qiu, Yun; Zhao, Jinhua
Abstract: We examine the distributional effects of high temperature on worker performance and the effectiveness of adaptation when capital investments such as air conditioning are not feasible. Using a longitudinal data set of 3196 professional archers in 57 competitions during 2010–2016 in China, which includes accurate performance measures at the individual‐by‐contest level, we show that heat causes more uneven performance distributions by hurting the bottom performers more than the top performers. More frequent heat reduces average performance and raises distributional inequality more than increases in average temperature. Gaining experience and long‐term acclimatization together can mitigate 70% of the heat impacts, demonstrating the potential of adaptation.